2019
DOI: 10.1039/c8cp07632d
|View full text |Cite
|
Sign up to set email alerts
|

Water adsorption, dissociation and oxidation on SrTiO3 and ferroelectric surfaces revealed by ambient pressure X-ray photoelectron spectroscopy

Abstract: Unveiling surface adsorbates under atmospheric conditions and in surface water redox reactions on TiO2 terminated surfaces and ferroelectric oxides, as studied by AP-XPS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 66 publications
3
56
0
Order By: Relevance
“…They also suggest that polarization orientation strongly influences the interaction of water molecules with the ferroelectric surface. [33][34][35][36] Near-ambient pressure X-ray photoelectron spectroscopy (AP-XPS), allowing the contributions of H 2 O and OH − groups to be considered separately, 15,17,37 has corroborated these observations, demonstrating an asymmetric adsorption of the charged species as a function of polarization orientation. 35,36 More recently, the combination of SPM with secondary ion mass spectrometry 38 has suggested that the evolution of chemical states during polarization switching, beside changes in surface chemistry, 39 can also include redistribution of bulk cations.…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…They also suggest that polarization orientation strongly influences the interaction of water molecules with the ferroelectric surface. [33][34][35][36] Near-ambient pressure X-ray photoelectron spectroscopy (AP-XPS), allowing the contributions of H 2 O and OH − groups to be considered separately, 15,17,37 has corroborated these observations, demonstrating an asymmetric adsorption of the charged species as a function of polarization orientation. 35,36 More recently, the combination of SPM with secondary ion mass spectrometry 38 has suggested that the evolution of chemical states during polarization switching, beside changes in surface chemistry, 39 can also include redistribution of bulk cations.…”
Section: Introductionmentioning
confidence: 84%
“…AP-XPS has the required chemical sensitivity to detect water molecules on the ferroelectric surface, whose adsorption and dissociation are well known to depend on the polarization 16,[33][34][35][36] as well as on surface chemical reactivity, 5,14,16,54 especially for perovskite oxides with TiO 2 terminated surfaces. 15 The total adsorption and the dissociation of water molecules into charged species (-OH groups, protons and peroxide species) is very different as a function of the as-grown sample polarization state. Fig.…”
Section: Surface Pzt Thin Film Chemical Composition By Ap-xpsmentioning
confidence: 99%
See 3 more Smart Citations